WOMEN’S VOICES IN ISLAMIC LITERATURE: NEGOTIATING TRADITION AND MODERNITY THROUGH LITERARY EXPRESSION - Jayanti, Anny Wahyu Dwi; Ahmadi, Anas; Darni, Darni; Subandiyah, Heny; Ilah, Muhammad Abdul (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
Islamic literature has a rich heritage of narratives that reflect the lives, values, and aspirations of Muslim societies. Within this framework, the role of women in Islamic literature offers an interesting view to study. This research aims to explore how Islamic literature reflects women’s experiences and how they navigate between tradition and modernity through their literary expression. A qualitative approach is used to analyze selected literary works from various cultural and geographical contexts in the Islamic world. Through in-depth text analysis, these findings provide insight into themes, characterizations, and narratives related to negotiating women’s identity in Islamic societies. By blending cultural, religious, and gender perspectives, this research explores the complexity of the relationship between women, tradition, and modernity in the context of Islamic literature. The results of this study are expected to provide a deeper understanding of the role of women in Islamic literature and the cultural dynamics that influence it. The implications of these findings could enrich discussions about gender, Islamic literature, and the relationship between tradition and modernity in the context of Muslim societies.